2021
DOI: 10.13057/biodiv/d220349
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics and taxonomic status of morphologically similar barnacles (Amphibalanus) assessed using the cytochrome c oxidase 1 gene

Abstract: Abstract. Riani S, Prabowo RE, Nuryanto A. 2021. Molecular characteristics and taxonomic status of morphologically similar barnacles (Amphibalanus) assessed using the cytochrome c oxidase 1 gene. Biodiversitas 22: 1456-1466. Amphibalanus variegatus and A. reticulatus have similar external morphology. Morphological similarities can be a severe problem for direct species-level identification. The problem can be overcome through anatomy-based identification and validated through molecular barcoding. Molecular cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This result is consistent with previous decisions on the taxonomic status of the samples, where they showed similar traits as the reference conspecific in the databases. Previous studies reported that a 3% genetic divergence is widely used in animal barcoding as a species border (Hubert et al 2012;Ko et al 2013;Mohammed et al 2021;Riani et al 2021). Several studies have also explored various thresholds as species border during molecular identification from less than 1% to 5% (Cote et al 2013;Aguilar et al 2017: Ha et al 2019Abdalwahhab et al 2020).…”
Section: Taxonomic Status Of Crustacean Larvaementioning
confidence: 99%
“…This result is consistent with previous decisions on the taxonomic status of the samples, where they showed similar traits as the reference conspecific in the databases. Previous studies reported that a 3% genetic divergence is widely used in animal barcoding as a species border (Hubert et al 2012;Ko et al 2013;Mohammed et al 2021;Riani et al 2021). Several studies have also explored various thresholds as species border during molecular identification from less than 1% to 5% (Cote et al 2013;Aguilar et al 2017: Ha et al 2019Abdalwahhab et al 2020).…”
Section: Taxonomic Status Of Crustacean Larvaementioning
confidence: 99%
“…Species identification and population genetic studies were conducted using various molecular markers (Nuryanto et al 2017;Butet et al 2019;Nuryanto et al 2019;Elvyra et al 2020;Riani et al 2021;Setyaningrum et al 2022). The cytochrome c oxidase 1 (COI) gene is a common marker used in species determination (Ko et al 2013;Muchlisin et al 2013;Dahruddin et al 2016;Irmawati et al 2017;Syaifudin et al 2020) and population genetic studies (Song et al 2013;Zhang et al 2014;Fahmi 2015;Nuryanto et al 2019).…”
Section: Classicalmentioning
confidence: 99%
“…A genetic threshold between 4% and 5% is permissible for genetic species determination, although additional considerations should be accounted for (Higashi et al 2011;Jeffrey et al 2011). Previous studies also utilized a genetic threshold of 5% during species determination (Candek and Kuntner 2015;Kusbiyanto et al 2020;Riani et al 2021).…”
Section: Amino Acid Compositionmentioning
confidence: 99%
“…Molecular biology is the science of organization, activity, and gene regulation on the molecular level [32]. Molecular biology can be used for species identification on the molecular level, which cannot be done at the level of morphological characteristics [33], [34]. At the molecular level, genetic diversity was becoming a challenge for determining the genetic structure and its relationship between environment, human activity, and impact on urbanization [35], also conservation success [36].…”
Section: Molecular Biology As the Key To Bioinformaticsmentioning
confidence: 99%